2018
DOI: 10.5249/jivr.v10i1.963
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and history of knee injury and its impact on activity limitation among football premier league professional referees

Abstract: Abstract:Background:The purpose of this study was to determine the epidemiology and history of knee injury and its impact on activity limitation among football premier league professional referees in Iran.Methods:This was a descriptive study. 59 Football Premier League professional referees participated in the study. The knee injury related information such as injury history and mechanism was recorded. Injury related symptoms and their impacts on the activity limitation, ability to perform activities of daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Our data reporting injuries and injury rates (1-year prevalence 36%; season prevalence 32.7%) are similar to injury rates for referees in other types of sports. In Iran’s Football Premier League, 6-month injury incidence was reported to be 22.4%, 31 out of 59 (56%) referees reported a history of knee injury, and injured referees reported decreased activities in daily and recreational living [ 4 ]. In Gaelic football, the annual injury prevalence was 58%, with 14% injured at the time of the survey [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our data reporting injuries and injury rates (1-year prevalence 36%; season prevalence 32.7%) are similar to injury rates for referees in other types of sports. In Iran’s Football Premier League, 6-month injury incidence was reported to be 22.4%, 31 out of 59 (56%) referees reported a history of knee injury, and injured referees reported decreased activities in daily and recreational living [ 4 ]. In Gaelic football, the annual injury prevalence was 58%, with 14% injured at the time of the survey [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports about injuries in soccer referees indicated that these referees resumed refereeing as early as one week after the injury occurred [ 11 ]. In some cases, the referees restarted with referring before the injury was cured or before injury related symptoms disappeared [ 4 , 7 , 11 ]. This insufficient recovery might increase the risk of a re-injury and therefore endangers referees’ health and well-being [ 4 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations